Analisis Manajemen Operasi menggunakan COBIT 5 – DS01 Manage Operation (Studi Kasus CV.XYZ) - Diana Trivena Yulianti; Adelia Adelia; Niko Ibrahim (Maranatha University Press, 2018)
CV. XYZ is an organization engaged in e-commerce, especially online hotel reservation. CV. XYZ uses and relies on information technology in carrying out organizational business activities. The use of information technology needs to be analyzed so that the use of information technology can be aligned with organizational goals, particularly the analysis of the application of controls related to information technology operations management. COBIT 5 - DS01 Manage Operation is used in analyzing information technology operations management to help organizations know the conditions related to information technology management operations in more detail.